Prices versus Quantities: The Political Perspective - Finkelshtain, Israel; Kislev, Yoav (Journal of Political Economy, 1997)
Regulation regimes subject to the influence of interest groups are compared. It is shown that the allocation of the regulated commodity varies with the implemented control and that the advantage of prices (vs. quotas) increases with the elasticity of the demand for or the supply of the commodity and decreases with the number of organized producers in the regulated industry. Control regimes can be ranked for negative, but not positive, externalities. Finally, a control regime leading to a more efficient commodity allocation also entails using fewer resources in rent-seeking activities.